FIRST RECORD OF BATHYTHRIX FORMOSA (DESVIGNES) (ICHNEUMONIDAE: CRYPTINAE) IN SERBIA (Acta Entomologica Serbica, 2018)
Bathythrix formosa (Desvignes, 1860) is a new finding of the ichneumonid wasp for the Serbian fauna. It was recorded on the locality Bojanine vode, Suva mt. Serbia from the host species Agroeca sp (Aranea: Liocranidae).